Architectural Features and Resistance to Food-Grade Disinfectants in Listeria monocytogenes-Pseudomonas spp. Dual-Species Biofilms - Rodríguez-López, Pedro; Rodríguez-Herrera, Juan José; López Cabo, Marta (Frontiers in Microbiology, 2022)
Listeria monocytogenes is still considered as a foodborne pathogen of serious concern capable to associate to other bacterial species, such as Pseudomonas spp., and adhere onto stainless steel (SS) surfaces. In an attempt to link the biofilms’ morphology and resistance to biocides, three different L. monocytogenes-Pseudomonas spp. biofilms were assayed to ascertain their morphological characteristics and resistance towards benzalkonium chloride (BAC) and neutral electrolysed water (NEW). Epifluorescence microscopy analysis revealed that each dual-species biofilms was distributed in a unique way over the SS surface and that these differences were attributable to Pseudomonas spp. Confocal laser scanning microscopy (CLSM) assays demonstrated that despite these differences in distribution all biofilms had similar maximum thicknesses. Moreover, colocalisation analyses showed a strong interrelationship of L. monocytogenes with Pseudomonas spp. but not vice versa, fact that was especially evident in those biofilms in which cell clusters were present. Finally, a modified Gompertz equation was used to fit biofilms’ BAC and NEW dose-response data. Outcomes demonstrated that L. monocytogenes was less susceptible to BAC when co-cultured with P. aeruginosa or P. fluorescens whereas susceptibility to NEW was reduced in all three dual-species biofilms that can be attributable to both the mechanism of action of the biocide and the architectural features of each biofilm. Therefore, results herein provided can be used to optimise already existing and develop novel sanitation treatments based on the biofilms’ composition and structure.